Multilingualism and Codeswitching in Language Acquisition - Dinar Dipta (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
There are more languages than the number of countries all over the world. This causes the existence of multilingualism in which a group of society can speak more than one language. Somehow, in the middle of the speech,  a speaker unintentionally and intentionally changes their language to the other language to highlight the speech or to make it easier to understand. Hence this paper reviews research findings on one of the key issues to which language contact in an educational setting has given rise, namely, the rationale for codeswitching practices in language acquisition. This is a library research presented in descriptive qualitative data. The data are taken from related literatures and observations. In particular, it reports on why bilingual teachers and students sometimes resort to codeswitching, and whether classroom codeswitching is an impediment or a resource to learning.